Pleurotheciaceae in Philippine freshwater ecosystems: new records, asexual morph report of Phaeoisaria filiformis, and phylogenetic assessment - Bagacay, Jan Felnesh Exe; Canto, Carr Marlo; Opiña, Lilcah Angelique; Nim, James Ariel; Velo, Jasmine; Lopez, Thomas Angelo; Ferriols, Victor Marco Emmanuel N.; Sadaba, Resurreccion B.; Calabon, Mark S. (Phytotaxa, 2025)
The study of lignicolous freshwater fungi in the Philippines led to the collection and isolation of two Pleurotheciaceae species, belonging to Rhexoacrodictys and Phaeoisaria. Phylogenetic analysis based on the internal transcribed spacer (ITS), beta-tubulin (TUB2), and RNA polymerase II (RPB2) loci revealed that UPVMI 24-0005 belongs to the taxon Rhexoacrodictys erecta, clustering closely with other strains (HSAUPmyr4622, IFRD500-016, HSAUP myr6489) (100% ML, 1.00 BYPP). UPVMI 24-006 was identified as Phaeoisaria filiformis, grouping with the holotype MFLUCC 18-0214 and KUNCC 23-13723 (90% ML, 1.00 BYPP). The present work also confirmed the first report of the asexual morphic stage of P. filiformis, as previous studies only described its sexual morph. Furthermore, the genus Saprodesmium, typified by S. dematiosporum, was transferred to Rhexoacrodictys based on multi-locus phylogenetic analysis, and the generic description is emended. The newly collected specimens represent novel records of Pleurotheciaceae in Philippine freshwater ecosystems. Detailed descriptions, illustrations, and multi-locus phylogenetic analysis of R. erecta and P. filiformis are provided.